Common active comorbid medical conditions among mental health users treated by the assertive community treatment team at Valkenberg Psychiatric hospital - Vlotman, Carmen Ilse (Department of Psychiatry and Mental Health, 2019)
Introduction People with severe mental illness have co-morbid medical conditions which are often undiagnosed and untreated leading to morbidity and mortality. Aims and Objectives The aim of this study was to investigate the documented rate of comorbid medical conditions in the Valkenberg Hospital Assertive Community Treatment (ACT) service population. The objectives were to determine the rate and type of comorbid medical conditions documented at the community clinic and to compare these findings with data recorded in the ACT services files. Analysis was undertaken to determine whether there was an association between the clinical measures and socio-demographic findings. Methods A descriptive, analytical, retrospective folder review was conducted on the ACT population of Valkenberg hospital. All clients treated by the ACT team between the 1st of January 2015 and the 31st of December 2015 were included in the study. The data was collected using a questionnaire. Results The ACT team treated 104 patients during the time of the study period. The age range was 21 to 63 years old (median 46). Thirty six of the patients were female (34.6%), sixty-eight (65.4%) were male. Substance use was documented in ninety-one (n=91) (87.5%) of all cases. Smoking was documented in sixty five (62.5%) of patients. Of the entire study sample, fifty-three patients (50.9%) had at least one medical condition. The most common active medical conditions documented at the patients’ combined treatment facilities were medication side-effects (22.3%), hypercholesterolemia (18.1%) and hypertension (10.6%). Significantly more medical conditions were recorded at Valkenberg hospital compared to the community clinics. There was an increase in metabolic illnesses in the middle age (44-53 years) group. Hypertension, diabetes mellitus and HIV appear to be slightly more common in females compared to males in this population. Discussion The study found comparatively low rates of medical conditions among the patients managed by the ACT team of Valkenberg hospital and the community clinics. These findings are not consistent with reviewed literature that found high rates of chronic medical conditions among people with severe mental illness. The rate of comorbid medical conditions is likely to be underestimated as they were not routinely screened for at both Valkenberg hospital and the community health centres. Conclusion The study highlights a gap between the management of mental illness and medical conditions in the ACT population. This has implication for the service provision of these clients in future.